THE EFFECT OF PANEL DISCUSSION ON THE STUDENTS’ READING COMPREHENSION - Syukri Iskandar; Sumarsih Sumarsih (Universitas Negeri Medan, 2017)
This study deals with the second year senior high school students’ in reading comprehension. The objective of the study was the investigation of the effect of Panel Discussion on the students’ in reading comprehension. The study was designed in experimental research. The population of this study was the 2015/2016 grade X students of SMA Swasta Dharmawangsa Medan. The total number of population of the study was 415 students which consist of 12 classes. The sample of the research was 60 students. The technique used for obtaining the sample was the cluster sampling technique. The sample classes were divided into two groups, namely the experimental group that was taught by applying Panel Discussion Technique, and the control group that was taught by applying classical Technique. The instrument for collecting data used objective test. The data were taken by administering the pre-test and post-test to both of experimental and control groups. The test was taken and selected from the National Examination test items that were related to the kind of narrative text. So, the validity and reliability of the test items were considered valid and reliable. The data were statistically analyzed by using t-test formula at the level of significance α (0.05) = 1.669 with the degree of freedom (df) = 65. It was found that the t-observed was higher than t-table (t-observed = 4.93 > t-table = 1.669; α = 0.05). It means that Panel Discussion Technique significantly affect the students’ achievement in reading comprehension. Keywords: Reading Comprehension, Cluster Sampling, Panel Discussion.